Abuse Of Investigator Authority In The Investigation Process Of Narcotics Crimes In Indonesia - Pahlevi, Harry (Jurnal Sostekmas: Jurnal Sosial, Teknologi, dan Pengabdian Masyarakat, 2026)
Investigators play a crucial role in determining the direction of drug crime investigations. However, abuse of authority frequently occurs, resulting in human rights violations and a decline in public trust in law enforcement. This study aims to analyze the legal accountability of investigators for abuse of authority in drug crime investigations in Indonesia. Using a normative juridical approach, this study examines the legal, philosophical, and sociological aspects. Legally, investigators can be held accountable for criminal, ethical, and administrative offenses. Philosophically, abuse of authority contradicts the principles of justice and legal morality. Sociologically, this phenomenon reflects weak internal oversight and a culture of impunity within the police institution. The results indicate that the oversight mechanism remains weak and ineffective in upholding investigator accountability. Transparent and independent oversight system reform is needed to achieve substantive justice.